The Effect of Aspirin to Reduced Incidence of Hepatocellular Carcinoma: A Comprehensive Systematic Review - Hatulely, Chrysman Andreria; Setiawan Nathan, Daniel (The International Journal of Medical Science and Health Research, 2024)
Background: Consistent aspirin usage is linked to a lower incidence of HCC in both the general population and certain populations that are at higher risk for the disease. Aspirin may also lessen the chance of HCC recurrence. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same  journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The use of aspirin has been linked to a significant, duration-dependent reduction in the risk of incident HCC. Therefore, to determine the clinical effectiveness and safety of aspirin usage for HCC chemoprophylaxis, it is imperative to conduct randomised placebo-controlled studies in well-phenotyped groups.